(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Although there has been momentum in implementing sexual and reproductive health (SRH) services in most countries, young people typically remain underserved by these services despite their demonstrated need. This study aimed to determine the factors influencing access to and utilization of youth-friendly sexual and reproductive health (AYSRH) services in Isiolo County. This study was conducted under the Jhpiego-supported Accelerating Post pregnancy Family Planning Integration into Primary Healthcare (APIP) project that supports Isiolo. Methods: Mixed-methods qualitative and quantitative approach​ was used. Data were collected using the KOBO digital tool. and analysis was performed using NVivo and Stata for qualitative and quantitative data, respectively. Results: The baseline study found that 69% of the APIP-supported facilities offered YFSRHS, with 77% of the facilities conveniently located for ease of access by the youths. 69% of the facilities had AYSRH signages displayed outside the buildings, with 31% displaying the signages inside the building. 31% of the facilities had separate counseling and examination rooms to ensure privacy for the youths as they sought services. 54% of the facilities involved the youth in decision-making during the provision of the YFSRHS. The study also found that 31% of the facilities involved their communities and made them aware of the YFHS provided at the hospitals. Conclusion: Interventions focusing on implementing YFSRHS should aim at addressing challenges affecting quality services in health facilities to offer them according to the youth’s needs.